Сравнительный анализ моделей конвективной теплоотдачи - Байда, Е.И. (Електротехніка і електромеханіка, 2011)
In the article, different models of convection heat emission by a heated object are considered. A comparative analysis of results obtained is conducted, quantitative results of calculations given.